1999
DOI: 10.1099/00221287-145-10-2797
|View full text |Cite
|
Sign up to set email alerts
|

The effect of motility and cell-surface polymers on bacterial attachment

Abstract: Recently it was shown that motility of Vibrio alginolyticus facilitated cell attachment to glass surfaces. In the present study the same relationship between motility and cell attachment was confirmed for Alcaligenes and Alteromonas spp. These findings clearly answer a long-standing question : does motility facilitate attachment ? However, they are contradictory to a general view on cell attachment that the energy barrier due to electrostatic repulsion between negatively charged bacterial cells and a glass sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(88 citation statements)
references
References 14 publications
2
84
1
1
Order By: Relevance
“…These have been attributed to the contribution of sedimentation phenomena at lower flow rates [35] and to presence of surface appendages, e.g. flagellum, which may have a positive effect on adhesion, a feature that is also not considered in this model [39]. Li, et al [35] have studied the contribution of sedimentation to mass transport in a PPFC using S. aureus and a glass surface.…”
Section: Discussionmentioning
confidence: 99%
“…These have been attributed to the contribution of sedimentation phenomena at lower flow rates [35] and to presence of surface appendages, e.g. flagellum, which may have a positive effect on adhesion, a feature that is also not considered in this model [39]. Li, et al [35] have studied the contribution of sedimentation to mass transport in a PPFC using S. aureus and a glass surface.…”
Section: Discussionmentioning
confidence: 99%
“…The above electrophoresis theory of soft particles has been applied to analyze the electrophoretic mobility data of biological colloids such as cells and their model particles [24][25][26][27][28][29][30][31][32][33][34][35]. Ohshima [36,37] proposed a theory of electrophoresis of soft particles in concentrated suspensions.…”
Section: Electrophoretic Mobility Of Soft Particlesmentioning
confidence: 99%
“…It is conceivable that in the contact region, that chargeable groups on the cell wall and Al2O3 surfaces have the same type of charge may be compensated by counterions, thereby preventing the generation of electrostatic repulsion. Kogure et al (1998) and Morisaki et al (1999) demonstrated that negatively charged Vibrio spp. cells could adhere to negatively charged glass surfaces by overcoming the energy barrier due to electrostatic repulsion between the cells and glass surfaces under high ionic strength when the cells were swimming at a high speed and had charged polymers at their surfaces.…”
Section: Introductionmentioning
confidence: 99%